2010
DOI: 10.1007/s11605-010-1211-1
|View full text |Cite
|
Sign up to set email alerts
|

High Hepatitis B Viral Load Predicts Recurrence of Small Hepatocellular Carcinoma after Curative Resection

Abstract: A retrospective cohort study was conducted to identify risk factors for recurrence of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) after curative resection. A total of 317 patients who had received curative resection of pathologically proven small HCC (< or = 3 cm in diameter) were analyzed to ascertain the factors affecting recurrence. The median follow-up period was 33.7 months. Cumulative recurrence rates at 1, 3, and 5 years after resection were 23.5%, 49.5%, and 65.5%, respectively. Male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 34 publications
(39 reference statements)
5
71
1
Order By: Relevance
“…Since we first reported that a high serum concentration of HBV DNA before surgery is a strong risk factor for HCC recurrence after curative resection for HBV-related HCC [4,10] , several studies have found similar results [11][12][13][14][15][16][17] . We also demonstrated that the lack of an acute exacerbation of hepatitis and a sustained low serum concentration of HBV DNA after surgery were significantly associated with a low risk for HCC recurrence [16] .…”
Section: Hbv-related Hccmentioning
confidence: 79%
“…Since we first reported that a high serum concentration of HBV DNA before surgery is a strong risk factor for HCC recurrence after curative resection for HBV-related HCC [4,10] , several studies have found similar results [11][12][13][14][15][16][17] . We also demonstrated that the lack of an acute exacerbation of hepatitis and a sustained low serum concentration of HBV DNA after surgery were significantly associated with a low risk for HCC recurrence [16] .…”
Section: Hbv-related Hccmentioning
confidence: 79%
“…31 The impact of viral factors on the recurrence of HCC after hepatectomy may be overshadowed by tumor-related factors during the early recurrence. 32 In conclusion, TFPI2 methylation in HCC plays a critical role in tumor invasion and progression. We provide evidence that TFPI2 methylation may be a predictor for poor postoperative outcomes and early tumor recurrence in patients with HCC after hepatectomy.…”
Section: Discussionmentioning
confidence: 90%
“…High hepatitis B viral load may suppress immunologic surveillance of cancer cells, leading to a higher recurrence risk. However, according several studies, a postoperative IFN-alpha antiviral treatment or a NAs therapy can significantly lower the rate of recurrence after hepatectomy [24][25][26][27]. Several other studies dispute this and, instead, found that antiviral treatment with nucleoside analogs failed to reduce the shortterm recurrence rate of postoperative patients with HBV-related HCC.…”
Section: Antiviral Treatment In Hepatectomymentioning
confidence: 99%